Fully differential ionization cross sections for proton collisions with multielectronic targets - Martínez, Sergio Hernán (2008)
In this work we present a theoretical study of the single ionization process involved in collisions of protons on He, Li, and Be targets at 2 MeV/amu projectile impact energy. Fully differential cross sections FDCSs are calculated within a continuum distorted wave method. Three different potentials are used to represent the interaction between the low energy outgoing electron and the residual ion target. Two of them are based on Coulomb potentials with proper effective charges for the target, while the other relies in a Garvey-type potential. These procedures provide remarkable differences in the binary and recoil peak regions, for the Li and Be cases. On the other hand, He target calculations lead to qualitative agreement for the three FDCSs at the momentum transfers and emission energies here considered. These results manifest the complexity of the ionization process for multielectronic targets and emphasize the importance of choosing an adequate model potential to describe the emitted electron dynamics in ionizing collisions.